До проблеми імплементації зарубіжного досвіду професійної підготовки поліцейських в українські правові реалії - Діденко, В. В.; Didenko, V. V. (Науковий вісник публічного та приватного права. - 2023. - Вип. 5. - С. 102-107, 2023)
Узагальнено найбільш позитивний зарубіжний досвід у сфері професійної підготовки поліцейських та можливості його імплементації в українські правові реалії. Наголошено, що в Україні, на прикладі провідних країн Європи, необхідно запровадити інститут професійної підготовки керівників. Констатовано, що доцільною є монополізація сектору професійної підготовки поліцейських шляхом наділення правом формувати професійні поліцейські кадри виключно спеціалізовані навчальні установи. Зроблено висновок, що важливою є зміна моделі професійної підготовки поліцейських, яка має прямо впливати на службову кар’єру.

The relevance of the article lies in the fact that the reform of law enforcement agencies of the state concentrates various legal and organizational processes aimed at building a new regulatory and legal basis for the activities of these agencies and ensuring the correct and effective coordination of the work of their representatives. One of the most important aspects of reform is always the study of foreign experience. This allows us to see how the work of law enforcement agencies is ensured in the territory of other states, to highlight positive examples of this experience for use in Ukrainian realities, as well as to get rid of clearly negative factors in advance that have a destructive effect on the internal system of ensuring law and order in the country. At the same time, the study of foreign approaches is effective not only in terms of improving the law enforcement sector as a whole, but also individual constituent bodies that are part of the law enforcement system, for example, the National Police of Ukraine. The purpose of the article is: to summarize the foreign experience of professional training of police officers and to work out the possibilities of its use in Ukraine. The article, based on the analysis of scientific views of scientists, summarizes the most positive foreign experience in the field of professional training of police officers in Ukrainian legal realities. It was emphasized that in Ukraine, following the example of leading European countries, it is necessary to introduce an institute for professional training of managers. It was established that it is expedient to monopolize the sector of professional training of policemen by granting the right to train professional police personnel exclusively to specialized educational institutions. It was concluded that it is important to change the model of professional training of police officers, which should directly affect the official career. In many foreign countries, taking a position specific to the nature of work, for example, a detective, obliges a police officer: first, to have work experience in the police profession; secondly, to have an appropriate level of education; thirdly, to complete a training course in specialized educational police institutions. Such a model is acceptable and effective for borrowing, but requires the following to be fixed at the legislative level: 1) gradation of the necessary experience of previous work in the police to occupy a position that involves work in a specific direction; 2) the requirement regarding the need to complete specialized courses before taking up positions that involve work in a specific direction. Such courses will make it possible to create a process of reorientation of police officers who seek to change the field of their official activity or advance in their official career.

Обобщен наиболее позитивный зарубежный опыт в сфере профессиональной подготовки сотрудников полиции и возможности его имплементации в украинские правовые реалии. Подчеркивается, что в Украине, по примеру ведущих европейских стран, необходимо внедрить институт профессиональной подготовки руководителей. Констатируется целесообразность монополизации сектора профессиональной подготовки сотрудников полиции путем предоставления права формирования профессиональных полицейских кадров исключительно специализированным учебным заведениям. Сделан вывод о необходимости изменения модели профессиональной подготовки сотрудников полиции, что должно напрямую влиять на служебную карьеру.
To the problem of implementation of foreign experience of professional training of police officers in Ukrainian legal realities
Keywords: професійна підготовка; працівники; поліцейські; зарубіжний досвід; імплементація; Національна поліція України; professional training; employees; police officers; implementation; foreign experience; National Police of Ukraine; профессиональная подготовка; полицейские; зарубежный опыт; имплементация; Национальная полиция Украины